Dampak pengendalian hama terpadu kakao terhadap serangan penggerek buah kakao (Conopomorpha cramella (Sn.)) (Lepidoptera : Gracillariidae) dan Helopeltis sp. (Hemiptera : Miridae) - Mujiono Mujiono; Tarjoko Tarjoko; Samuji Samuji (Perhimpunan Entomologi Indonesia, 2005)
Impact of integrated Pest management (IPM) for cacao pod borer attack (Conopomorpha cramella (Sn.)) (Lepidoptera: Gracillariidae) dan Helopeltis sp.(Hemiptera : Miridae). Research on impact of integrated Pest management (IPM) for cacao pod borer attack (Conopomorpha cramella (Sn.)) and Helopeltis sp. had been conducted at Tumbik Melayu Village, Teluk bayur District, Berau Regency, in East Kalimantan, starting from May to September 2002. It used nested classification design. IPM practices applied in this research were pruning, balanced fertilization, weeding, field sanitation (leaf mulch), light pruning, fregment harvesting (every week), burrying of pod shell, and wrapping of young pod in week 15th. Result of the research revealed that IPM application could reduce the cacao pod borer attack reaching: a) light category before treatments from 41.29 to 15.00%; b) heavy category before treatments from 20.56 to 0 and 23.37%, compare to farmer plot. IPM implementation were able to increase percentage of healthy pod up to 18.66% compared to farmer plot. Beside it could suppers development of Helopeltis sp. population up to 24%. The dominant natural enemies were spider as many as 1.34 individuals per plant on IPM plot and 0.6 spider per plant on farmer plot (non IPM). Application of IPM practices were able to increase agronomic character: a) number of flower up to 37.22% when compare to farmer plot, and b) number of fruits until 5.56%, whereas number of young fruits decrease up 13.25%.